Two ways to be a velvet worm - Monge, Julián (2019)
There are two ways to be a velvet worm. One is to mate vaginally at a young age, give birth in any month and have small, scarce males. The other is to periodically inseminate through the body wall, with sexual equality in size and abundance. The second way seems to be an evolutionary adaptation to habitats that are colder and drier than the habitats of neotropical velvet worms.